2006
DOI: 10.1177/0092055x0603400103
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Data Analysis (IDA): Working With Sociology Departments to Address the Quantitative Literacy Gap

Abstract: Network sought to close the quantitative literacy gap for sociology majors. Working with twelve departments, the project built on lessons learned from ASA's Minority Opportunities through School Transformation (MOST) Program, where curricular change was a departmental (not individual faculty) agenda. A critical mass of faculty in each IDA department developed and used quantitative modules in lower division courses. This article reports on the steps to develop departmental curricular change and the important re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 17 publications
0
70
0
Order By: Relevance
“…Existing pedagogical research (Finkelstein 1994;Bridges et al 1998;Howery and Rodriguez 2006) and guidelines from the American Sociological Association (Sociology Task Force 1991;McKinney et al 2004) tell us that adequate statistics training in the sociology major is integral to preparing our graduates for their futures as citizens, scholars, and employees. Social Statistics for a Diverse Society, a textbook for statistics in sociology departments, reads "Statistics can help us gain insight into real-life problems that affect our lives" (FrankfortNachmias and Leon-Geurrero 2015, xv).…”
Section: Teaching Statistics To Sociology Majorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Existing pedagogical research (Finkelstein 1994;Bridges et al 1998;Howery and Rodriguez 2006) and guidelines from the American Sociological Association (Sociology Task Force 1991;McKinney et al 2004) tell us that adequate statistics training in the sociology major is integral to preparing our graduates for their futures as citizens, scholars, and employees. Social Statistics for a Diverse Society, a textbook for statistics in sociology departments, reads "Statistics can help us gain insight into real-life problems that affect our lives" (FrankfortNachmias and Leon-Geurrero 2015, xv).…”
Section: Teaching Statistics To Sociology Majorsmentioning
confidence: 99%
“…Yet instructors teaching statistics in sociology departments face a number of challenges, and an ASA review of sociology major curricula found insufficient statistics training early on, a lacuna they referred to as a "quantitative literacy gap" (Howery and Rodriguez 2006). The infamous "statistics anxiety" that robs students of confidence in their ability to succeed continues to plague statistics classrooms (Bridges et al 1998;Onwuegbuzie and Wilson 2003;Van Gundy et al 2006;Delucchi 2014).…”
Section: Teaching Statistics To Sociology Majorsmentioning
confidence: 99%
See 3 more Smart Citations